Design Synthesis of 5.8 GHz Octagonal AMC on a Very Thin Substrate - Abu, Maisarah; Hussin, Eryana Eiyda; Rahmalan, Hidayah; Munawar, Rose Farahiyan (2015)
This paper proposed a development of 5.8 GHz Artificial Magnetic Conductor, AMC using very thin substrate with thickness of 0.13 mm. Different shapes of PEC metallization are discussed in order to achieve the highest bandwidth of unit cell AMC. Another approaches for increasing the bandwidth is by applying the ring patch around the substrate as well as implementing the DGS ground plane. The proposed design produces 1.96 % bandwdith of unit cell. Applying the 2 x 4 unit cell arrangement gives the best result for directivity equal to 6.75 dBi, gain of 6.83 dB, efficiency = 98.41 % and return loss = -45.63 dB.